Kant in Spanish: the problem of the Latin-Germanic doublets exemplified in the case of Gegenstand/Object - Vázquez Lobeiras, María Xesús (Con-Textos Kantianos. International Journal of Philosophy, 2024)
This article considers the problem of the occurrence of Latin-Germanic terminological doublets in Kant's Critique of Pure Reason. A detailed analysis of the Prefaces to the first and second edition, as well as of the pages of the Transcendental Deduction of the categories in both versions, supports the conclusion that, despite Kant's fluid and unruled use of the two terms, they cannot always and in all cases be considered synonymous. On the contrary, there are very significant passages that point to the need to differentiate the two terms in translation. On the basis of this analysis, a proposal is made for a convention that could be used for this purpose.